Hubungan Mindful Eating dan Kebiasaan Jajan dengan Status Gizi (IMT/U) pada Siswi Kelas XII IPS di SMA Negeri 14 Kota Tangerang - Safira Salsabila (2021)
Adolescents among the vulnerable groups affected by nutritional problems along with increased physical growth. One of them is nutritional status, namely good nutritional status, poor nutritional status, and lack of nutrition. Assessment of nutritional status using anthropometry with BMI/Y measurement. An increased BMI can result from mindless eating or unfocused eating. Mindful eating can overcome healthy eating arrangements or an increased BMI. In addition, adolescent girls consume more snacks such as sweet foods, fatty foods, salty foods, than men. Lack of knowledge in choosing snack foods so having bad snacking habits can lead to obesity. The purpose of this study was to determine the relationship between mindful eating and snacking habits with nutritional status (BMI / U) on female student in class XII IPS SMA Negeri 14 Kota Tangerang. The research method used a quantitative approach with a cross-sectional design. The study population was female students of class XII IPS at SMA Negeri 14 Kota Tangerang with a research sample of 42 respondents and used a stratified random sampling technique. The data analysis in this study used the chi-square statistical test and the Pearson test. The results of the bivariate data analysis showed that there was no relationship between mindful eating (p = 0.439) and snacking habits (p = 0.601) and nutritional status (BMI/Y) on female student in class XII IPS SMA Negeri 14 Kota Tangerang.